2012
DOI: 10.3762/bjoc.8.85
|View full text |Cite
|
Sign up to set email alerts
|

Identification and isolation of insecticidal oxazoles from Pseudomonas spp.

Abstract: SummaryTwo new and five known oxazoles were identified from two different Pseudomonas strains in addition to the known pyrones pseudopyronine A and B. Labeling experiments confirmed their structures and gave initial evidence for a novel biosynthesis pathway of these natural oxazoles. In order to confirm their structure, they were synthesized, which also allowed tests of their bioactivity. Additionally, the bioactivities of the synthesis intermediates were also investigated revealing interesting biological acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…During our screening for novel natural products by UPLC‐ESI‐MS of XAD‐16 extracts17 from Xenorhabdus cultures in standard LB medium we identified a new family of natural products. According to characteristic neutral losses for amino acids such as valine, leucine, and isoleucine in their MS 2 fragmentation patterns, these compounds were identified as peptides 18.…”
Section: Resultsmentioning
confidence: 99%
“…During our screening for novel natural products by UPLC‐ESI‐MS of XAD‐16 extracts17 from Xenorhabdus cultures in standard LB medium we identified a new family of natural products. According to characteristic neutral losses for amino acids such as valine, leucine, and isoleucine in their MS 2 fragmentation patterns, these compounds were identified as peptides 18.…”
Section: Resultsmentioning
confidence: 99%
“…associated with entomopathogenic nematode (Grundmann et al, 2012). These compounds showed significant MICs against Gram-positive bacteria, including S. aureus, B. subtilis , methicillin-resistant S. aureus and Enterococcus faecium (MIC value: 2–4 μg/ml) and reasonable activity against E. faecalis and S. pneumoniae (MIC value: 16–64 μg/ml) with being the more active of the two compounds (Giddens et al, 2008; Singh et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…It was previously reported that the metabolites produced by Pseudomonas sp. have insecticidal activity (Grundmann et al, 2012). The secondary metabolites produced by bacteria such as Photorhabdus sp.…”
Section: Resultsmentioning
confidence: 99%